2018
DOI: 10.2169/internalmedicine.0033-17
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management of Pregnancy in a Patient with Systemic Lupus Erythematosus-associated Pulmonary Arterial Hypertension

Abstract: Pregnancy in women with systemic lupus erythematosus (SLE)-associated pulmonary arterial hypertension (PAH) remains a high risk. We successfully managed a pregnancy in a patient with SLE-PAH. A 31-year-old pregnant woman with SLE-PAH had worsening PAH and SLE flare-up during pregnancy and a sudden increase in pulmonary arterial pressure after delivery. SLE-PAH was controlled by continuous intravenous epoprostenol and inhaled nitric oxide therapy combined with high-dose corticosteroids under close hemodynamic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…A review of the literature included 14 pregnancy cases complicated by SLE-PAH in 11 studies from 2002 to 2021 13–18 24–28. Most patients (except for the case in Zhou et al 24) delivered via caesarean section (76.92%); the others delivered vaginally (23.08%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A review of the literature included 14 pregnancy cases complicated by SLE-PAH in 11 studies from 2002 to 2021 13–18 24–28. Most patients (except for the case in Zhou et al 24) delivered via caesarean section (76.92%); the others delivered vaginally (23.08%).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, few publications and guidelines have focused on decision-making and management of pregnancy in women with SLE-PAH. Several recent case reports have shown that pregnancy is feasible in patients with SLE-PAH 13–20. These investigations suggested the possibility of successful pregnancy complicated by SLE-PAH and served as the foundation for future management and treatment guidelines.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Importantly, in the last 2 decades, there have been multiple modern case reports and case series that have reaffirmed the safety and efficacy with the use of epoprostenol in parturients with pulmonary hypertension without evidence of preterm labor, bleeding complications, and/or detrimental fetal effects (5,(9)(10)(11)(12)(13)(14). The clinical efficacy, evidence for safety, and lack of demonstrated harm with exposure to IV or aerosolized epoprostenol in human studies has led to the recommendation for its use as first line in pregnant women with pulmonary hypertension (15).…”
mentioning
confidence: 99%